Implementasi Pembelajaran TIK: Pendampingan Penggunaan Microsoft Word sebagai Media Penunjang Belajar Siswa SD NEGERI 2 Mersi - Tsuroya Salmah; Meli Lestari; Yumna Azizah; Nadea Nawal Syefira; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
In the current digital era, computer proficiency has become an essential basic skill for children, even at the elementary school level. However, many students still lack the opportunity to explore word processing software in depth. This program was initiated to provide hands-on mentoring in the use of Microsoft Word for students at SD NEGERI 2 MERSI. Using a